Policy Coordination on Transportation Infrastructure Development in Palembang City - Zakir, Syaifudin; Maksum, Irfan Ridwan; Kurniawan, Teguh (Khazanah Sosial, 2024)
On a national level, Palembang is positioned to support various spatial and developmental needs of Jakarta, the capital city. Hosting the Asian Games 2018 was one such initiative, which necessitated accelerated transportation infrastructure development in Palembang. This required innovative approaches to policy coordination in infrastructure development. This study aims to examine the mechanisms and challenges of policy coordination in transportation infrastructure development. The research highlights that coordination efforts have faced delays due to institutional constraints, as agencies and institutions are tied to their own regulations, budgets, and programs while striving to meet their individual targets. Adopting a post-positivist approach, this study employs qualitative methods, including in-depth interviews with stakeholders, and applies qualitative data analysis techniques. The findings reveal that coordination challenges have been mitigated to some extent through the national strategic development project framework, with the entire coordination process being directed by a top-down approach led by the Committee for the Acceleration of Infrastructure Provision (KKPPI).